Combination Tones in Violins - LOHRI, Angela; CARRAL, Sandra; CHATZIIOANNOU, Vasileios (Archives of Acoustics, 2011)
In this study we investigate the appearance of combination tones in violins. Mostauthors in recent times have emphasised that combination tones occur inside theear exclusively (intra-aural). This assumption will be subjected to scrutiny basedon evidence found in an empirical study in which combination tones were measuredoutside the ear (extra-aural).Measurements were performed in which a violinist played two tones of a partic-ular musical interval simultaneously. This was recorded and subsequently analysedusing a Fourier Transformation. In addition to the partial tones of the primaryinterval, the resulting spectrum showed frequencies corresponding to combinationtones. Similar measurements on the viola and violoncello also revealed the exis-tence of extra-aural combination tones. Such frequencies may influence the timbreof simultaneous intervals played on string instruments. In another experiment theviolin was excited using an electrodynamic mini-shaker with the aim of localisingthe origin of extra-aural combination tones. A newly devised tone matrix was usedas a theoretical approach which computes all potential combination tones that mayoccur between any pair of partial tones. The detailed analysis of musical intervalsby both the frequency spectrum and the tone matrix shows characteristic mirrorand point symmetries in the partial tone structure. The discussion focuses mainlyon the audibility of extra-aural combination tones and on ‘the combination tone 1’.This research opens up new perspectives and questions relevant for interpreters,composers, violin makers and violin acousticians.